2015
DOI: 10.1007/s41030-015-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit of Repeated Dry Powder Inhaler’s Inhalation Technique Counseling on Asthmatic Patients

Abstract: The aim of the work presented here was to determine the role of dry powder inhaler (DPI) counselling on inhalation technique and lung function test scores of the asthmatic patients. To decrease variability, asthmatic patients using an Aerolizer were enrolled in the study, as this was the most commonly prescribed DPI in outpatient clinics of Beni Suef University hospital. Each patient was subjected to three visits separated by 1 month each. In each visit, patient inhalation technique from the DPI was checked, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Similar to earlier studies, 5,42,43 the results showed that a high number of subjects using MDI did not achieve MDI inhalation technique correct in the visit 1 but they significantly got better in the visit 2 ( P < .001) and improved more in the visit 3 ( P < .001) 14,24,26‐28,32 . Therefore, continuous counselling of the asthmatic subjects significantly correlates with the proper MDI inhalation technique ( P < .001) 24,29,44‐46 . Additional care should be given to this counselling after observing the results of the first group which did not improve at all with 95 subjects dropping out of the study 34 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to earlier studies, 5,42,43 the results showed that a high number of subjects using MDI did not achieve MDI inhalation technique correct in the visit 1 but they significantly got better in the visit 2 ( P < .001) and improved more in the visit 3 ( P < .001) 14,24,26‐28,32 . Therefore, continuous counselling of the asthmatic subjects significantly correlates with the proper MDI inhalation technique ( P < .001) 24,29,44‐46 . Additional care should be given to this counselling after observing the results of the first group which did not improve at all with 95 subjects dropping out of the study 34 .…”
Section: Discussionsupporting
confidence: 77%
“…Continuous counselling of asthmatics improves their long‐term asthma control and has vital role in the proper managing of various limitations of airflow 16‐18 . It also may increase the pulmonary function tests score, quality of life and asthmatic subjects’ illness 19‐32 …”
Section: Introductionmentioning
confidence: 99%
“…Although systemic delivered therapy is available for asthma and chronic obstructive pulmonary disease (COPD), inhaled therapy is the most widely used option [1][2][3]. The reason behind that is the better safety index for the inhaled way [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaler technique needs to be checked and education repeated over time. It is now well established that having the physical skill to use an inhaler does not guarantee that a patient will continue to use an inhaler correctly over time, with approximately 50% of patients failing to maintain correct inhaler technique over time [54][55][56][57][58]. While there are tools that can be used in addition to physical demonstration to improve this [59], the starting point is a follow-up of inhaler technique over time by the health care practitioner.…”
Section: What Do Health Care Practitioners Need To Consider In Addresmentioning
confidence: 99%